Digital Marketing: Impact on Spa Businesses: Digital Marketing: Impact on Spa Businesses - Bunchaliao, Piyanee; Pakittawichit, Thananchakorm; Satieramas, Sunanta (RATANABUTH JOURNAL, 2024)
Digital Marketing is Significantly Transforming the Spa Industry. Studies reveal that 82% of consumers search for spa service information online before making a decision. Leveraging digital marketing tools, including social media, SEO, and email marketing, enhances brand awareness and maintains customer loyalty. As a result, spas that embrace digital transformation experience a growth rate 30% higher than the industry average. Despite challenges in workforce skill development and customer data management, digital marketing has become a critical factor for the survival of spa businesses. This article analyzes the impact of digital marketing on the spa industry and proposes strategies for sustainable growth in the digital era. This article aims to analyze the impact of digital marketing on spa businesses in an era where digital technology is rapidly transforming the business landscape. The primary objective is to explore effective digital marketing strategies for spa businesses and assess their effects on operations and performance. The use of digital marketing tools, such as social media marketing, Search Engine Optimization (SEO), and email marketing, has shown a significant positive impact on brand awareness, attracting new customers, and retaining existing ones. Spa businesses that effectively implement digital marketing strategies demonstrate higher revenue growth rates than the industry average. Moreover, the application of AI and Machine Learning technologies in customer data analysis has proven effective in improving website visitor conversion rates and increasing the average purchase value per transaction. However, the study also highlights challenges faced by spa businesses in adapting to digital marketing, including a lack of digital skills among staff and managing online customer data.This article presents a model illustrating the impact of digital marketing on spa businesses in five key areas: consumer behavior, brand awareness, operational efficiency, customer experience, and market expansion. The model helps spa entrepreneurs gain a clearer understanding of the relationship between the use of digital marketing tools and business outcomes.